2005
DOI: 10.1007/s11104-004-1610-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transgenic plants on soil microorganisms

Abstract: The rapid development of agricultural biotechnology and release of new transgenic plants for agriculture has provided many economic benefits, but has also raised concern over the potential impact of transgenic plants on the environment. Considerable research has now been conducted on the effects of transgenic plants on soil microorganisms. These effects include unintentional changes in the chemical compositions of root exudates, and the direct effects of transgenic proteins on nontarget species of soil microor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
73
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 71 publications
4
73
0
3
Order By: Relevance
“…This study is the first to evaluate the impact of Bt white spruce, or any other Bt plant, on nitrogenfixing communities. No effect associated with the presence of the B. thuringiensis transgene was observed in this study, which is in agreement with other recent studies evaluating the impact on overall bacterial diversity (1,3,4,10,12,23,26,32). On the other hand, significant differences were found between diazotroph communities associated with white spruce in natural stands and those associated with trees in a plantation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study is the first to evaluate the impact of Bt white spruce, or any other Bt plant, on nitrogenfixing communities. No effect associated with the presence of the B. thuringiensis transgene was observed in this study, which is in agreement with other recent studies evaluating the impact on overall bacterial diversity (1,3,4,10,12,23,26,32). On the other hand, significant differences were found between diazotroph communities associated with white spruce in natural stands and those associated with trees in a plantation.…”
Section: Discussionsupporting
confidence: 93%
“…Particular attention was paid to studying the impact of Bt plants, which constitutively express the Cry1Ab insecticidal toxin of Bacillus thuringiensis, on rhizosphere microbial communities. Although studies demonstrating a negative impact of Bt crops on soil microbiota exist (7,44), more studies showing no effect have been published (1,3,4,10,12,23,26,32).…”
mentioning
confidence: 99%
“…Any change in the quality of root exudates can modify the composition of the biota in soil (biodiversity), as well as their activity (Stotzky 2004;Patra et al 2006), and may produce deleterious or beneficial changes in the microbiota (Wei et al 2006;Griffiths et al 2006). To date, there has been limited research to investigate the influence of Bt-crops and Bt-toxins on soil processes (see Bruinsma et al 2003;Dunsfield and Germida 2004;Stotzky 2004;O'Callaghan et al 2005;Liu et al 2005;Fang et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on impact of transgenic crops on soil properties carried out were restricted to contained or controlled conditions (Liu et al 2005). Although some research has examined the environmental impacts of the 'aboveground' portion of transgenic crops, relatively fewer research effort has focused on the effects of these crops on soil microbes (Bruinsma et al 2003) although no risk of growing transgenic Bt cotton on soil health is reported (Sun et al 2007, Sarkar et al 2009).…”
mentioning
confidence: 99%